OP47 Relationships between sugar intake from sweet food and beverages, common mental disorder and depression: prospective findings from the whitehall ii cohort study. (2nd September 2017) - Knüppel, A; Shipley, MJ; Llewellyn, CH; Brunner, EJ
Abstract : Background: In the face of high rates of mood disorders and an overconsumption of sugar, intake of sweet food, beverages and added sugars has been linked with depressive symptoms in several populations. It remains unclear if this association is causal or due to reverse causation (the influence of mood on sugar intake). Our study aimed to investigate systematically cross-sectional and prospective associations between sugar intake from sweet food/beverages, common mental disorder (CMD) and depression, and to examine the role of reverse causation as potential explanation for the observed linkage. Methods: We analysed repeated measures (23 245 person-observations) from the Whitehall II cohort study. The study recruited non-industrial civil servants from 1985 to 1988. The most recent data used in this analysis was collected in 2013. CMD was measured with the 30-item General Health Questionnaire and depression with the 20-item Centre for Epidemiologic Studies Depression scale. Sugar intake from sweet food/beverages was assessed using food frequency questionnaires. Prospective analyses included 2, 5 and 10 year follow-up periods. We modelled associations using random effects regression using Stata 14. Results: Cross-sectional analyses showed positive associations. In prospective analyses we found a positive association of sugar intake from sweet food/beverages with incident CMD in men and with recurrent depression in women. Men in the highest tertile of intake had a 24% increased odds of incident CMD after 5 years (95% CI: 1.02, 1.48) independent of health behaviours, socio-demographic and diet-related factors, adiposity and other diseases (fully adjusted model). Women had a 36% increased odds for recurrent depression per 30 g increment (95% CI: 1.03, 1.80) in fully adjusted models, associations using tertiles of sugar intake from sweet food/beverages were similar but not statistically significant when adjusted for diet-related factors. Notably, neither CMD nor depression predicted changes in sugar intake from sweet food/beverages. Conclusion: Our findings using repeated measures follow-up data over 22 years suggest an adverse effect of sugar intake from sweet food/beverages on long-term psychological health. These results add further support for public health interventions which promote reduced sugar intake to improve overall health.